(untitled) (El-Wahat Journal for Research and Studies, 2015)
This study aims to attempt to go into the concepts of innovative activities and the positioning process, to find out the options level of strategic positioning in light of recourse business organizations to head towards innovative activity, to create competitive advantage with enhancing the marketing intelligence systems and exploit the available opportunities in the market. The business organizations managers understand to they are obliged to stimulating of innovative activities in order to identify the favorable results with respect to strong positioning in the market, brand or product .Our study has concluded that, no organization can position itself in light of a marketing environment which is complex and variable usually, whatever dedicated its innovative marketing without activating this activity and control it. Key words: innovation marketing, positioning, market retail, marketing process.